Evaluating muscle characteristics and fall events: insights from real-world longitudinal data - Shaofang Li; Juchuan Dong; Caixia Zhao; Yongmei Li; Wenyuan Wang; Lijuan An; Yongqian Han; Fuhou Zhang; Lihua Jin (Annals of Medicine)
Background To compare the relationship between the delta values of muscle quantity (thickness) and muscle quality (grayscale) in the paretic and nonparetic lower extremities and the incidence of falls within 3 months. Muscle quality and quantity can significantly influence lower limb muscle strength in patients, potentially contributing to fall-related incidents.Setting Rehabilitation department of the largest rehabilitation center in Southwest China’s Yunnan Province.Participants Patients with hemiplegic stroke or traumatic brain injury within the preceding 3 months. Exclusion criteria included the presence of other primary diseases that could contribute to muscle loss.Main outcome measures Baseline characteristics, muscle thickness and grayscale measurements, inflammatory biomarkers, and total cholesterol levels were collected to evaluate patient-specific factors associated with subsequent falls after a 3-month period.Results Compared with patients with a manual muscle testing (MMT) score ≥3, those with an MMT score <3 exhibited significant differences in the rectus femoris (RF) (p = 0.002) and long head of biceps thickness of the affected limb (p = 0.033). The vastus intermedius, gastrocnemius (GM), and vastus medialis were more prominent in patients with an MMT score ≥3 (p = 0.045, 0.005, and 0.032, respectively). The primary distinction between the affected and unaffected limbs in both MMT groups was observed in the delta values of grayscale rather than in muscle thickness. Notably, 38.8% of patients with an MMT score <3 experienced at least one fall over 3 months, compared with an 8.69% fall rate among those with an MMT score ≥3 (p = 0.028). Initial changes in procalcitonin and cholesterol levels exhibited a stronger correlation with gait function than baseline measurements of muscle thickness or grayscale. The delta values in RF muscle thickness and delta value of GM grayscale were significantly associated with the incidence of subsequent falls after 3 months period.Conclusion Real-world, longitudinal data suggest that muscle grayscale, rather than muscle thickness, may offer superior prognostic insights. The likelihood of a falling event was elevated in patients with an MMT score <3, particularly among those with significant disparities in GM grayscale values between affected and unaffected limbs.